An architecture for the optimal control of tertiary and secondary levels in small-size islanded microgrids. (December 2018) - Delfino, Federico; Ferro, Giulio; Robba, Michela; Rossi, Mansueto
Highlights: This paper proposes a new hierarchical architecture for islanded microgrids using a Model Predictive Control approach. An optimization problem is formalized for tertiary and secondary control. The results are validated using real data on an electromagnetic simulator. Abstract: Islanded microgrids are assuming a key role for the support in the distribution grid's management, which is more and more difficult due to the massive increase of distributed generation and energy production plants from renewable resources. In this paper, a new architecture for the optimal control of tertiary and secondary levels in small-size islanded microgrids is proposed. Specifically, at each optimization step, by using a receding horizon approach, the tertiary control provides the optimal power schedule for the microgrid on the basis of economic and environmental criteria. Then, the secondary control, to provide set points for primary control, uses another objective function that minimizes the quadratic deviation from the reference values provided by the tertiary level and the desired frequency for good performances. The approach is applied to a real case study (a portion of the Savona Campus Smart Polygeneration Microgrid) characterized by a diesel engine connected to a synchronous generator, a photovoltaic plant, and an electrical storage system.